Mineralization of gellan gum hydrogels with calcium and magnesium carbonates by alternate soaking in solutions of calcium/magnesium and carbonate ion solutions. (27th June 2018) - Lopez‐Heredia, Marco A.; Łapa, Agata; Reczyńska, Katarzyna; Pietryga, Krzysztof; Balcaen, Lieve; Mendes, Ana C.; Schaubroeck, David; Van Der Voort, Pascal; Dokupil, Agnieszka; Plis, Agnieszka; Stevens, Chris V.; Parakhonskiy, Bogdan V.; et al.
Abstract: Mineralization of hydrogels is desirable prior to applications in bone regeneration. CaCO3 is a widely used bone regeneration material, and Mg, when used as a component of calcium phosphate biomaterials, has promoted bone‐forming cell adhesion and proliferation and bone regeneration. In this study, gellan gum hydrogels were mineralized with carbonates containing different amounts of calcium (Ca) and magnesium (Mg) by alternate soaking in, firstly, a calcium and/or magnesium ion solution and, secondly, a carbonate ion solution. This alternate soaking cycle was repeated five times. Five different calcium and/or magnesium ion solutions, containing different molar ratios of Ca to Mg ranging from Mg free to Ca free were compared. Carbonate mineral formed in all sample groups subjected to the alternate soaking cycle. Ca : Mg elemental ratio in the mineral formed was higher than in the respective mineralizing solution. Mineral formed in the absence of Mg was predominantly CaCO3 in the form of a mixture of calcite and vaterite. Increasing the Mg content in the mineral formed led to the formation of magnesian calcite and decreased the total amount of the mineral formed and its crystallinity. Hydrogel mineralization and increasing Mg content in mineral formed did not obviously improve proliferation of MC3T3‐E1 osteoblast‐like cells or differentiation after 7 days.